Kajian Kemampuan Berpikir Kreatif dalam Pembelajaran Matematika di Sekolah Menengah Pertama pada Materi Geometri - Yasintha Esterina Klau; Siprianus Suban Garak; Damianus D. Samo (Universitas Nusa Cendana, 2022)
This study aims to describe the conception of creative thinking ability in mathematics and describe the application of creative thinking in mathematics learning for students at junior high school. The method used in this paper is literature study, which is carried out by tracing various reference libraries in the form books, and articles/journals. Based on the theories studied, it is concluded that creative thinking ability is the ability to think logically and divergently to generate ideas or various kinds of answers to a given mathematical problem, where a given mathematical problem can be solved with more than one solution and through fluent thinking, flexible, elaborating and having originality in the solution. Creative thinking has an important role in learning process. The application of creative thinking in mathematics learning requires teachers to be able to design learning that is able to open opportunities for the creation and development of students' mathematical creative thinking ability. In the learning design that is prepared, it must involve creative problems that lead students to think creatively so that it can lead to increasing students' creative thinking ability